APPLICATION OF DWANGSOM (COERCED MONEY) IN DISPUTE RESOLUTION BREACH OF PAYMENT OF SHARIA LIFE INSURANCE CLAIMS (Study of Supreme Court Decision Number 364 K/Ag/2023) - Firdiansyah Hidayatullah; Moh. Fadli; Sihabudin (CV. RADJA PUBLIKA, 2025)
The ruling in the Supreme Court Decision Number 364 K/Ag/2023 contains a penalty of payment of a sum of Rp538,178,014.00 (five hundred thirty-eight million one hundred seventy-eight thousand and fourteen rupiah) and also contains a penalty of dwangsom (forced money) to the defendant/applicant of cassation in the amount of Rp100,000.00 (one hundred thousand rupiah) for each day the defendant is late in carrying out the contents of the decision that has obtained permanent legal force. If referring to the norm in Article 606a Rv, the judge can only impose a penalty of dwangsom (forced money) if the judge's decision contains a penalty other than the penalty of paying a sum of money. The deviation in the application of the penalty of dwangsom (forced money) in the decision is based on considerations of justice and legal benefits as contained in the legal considerations. The research method in this writing is a normative legal research method by analyzing legal norms with legal principles. The purpose of this writing is to provide an understanding of the judge's authority in imposing a dwangsom (forced money) penalty in a default decision which includes a penalty of payment of a sum of money in a sharia life insurance case which is guided by the principles of justice, legal benefit, and the principle of ta'awun (mutual assistance).